FRI0260 Polymorphisms of stat4 and mir146a predict the achievement of 5 years remission in patients with systemic lupus erythematosus. (12th June 2018) - Perricone, C.; Ciccacci, C.; Ceccarelli, F.; Mettola, G.; Leccese, I.; Spinelli, F.R.; Alessandri, C.; Politi, C.; Latini, A.; Novelli, G.; Valesini, G.; Borgiani, P.; et al.
Abstract : Background: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease with a complex pathogenesis in which genes and environmental factors interact leading to a protean clinical picture. Treat-to-target recommendations have identified 'remission' as a target in SLE, since achievement of remission improves the outcome and is associated with decreased damage progression. Nonetheless, predicting factors for the achievement of remission are lacking. It is likely that genes associated with SLE pathogenesis may influence the disease course. Objectives: Thus, our aim was to analyse previously identified loci associated with SLE in a cohort of SLE patients to evaluate their influence on remission achievement. Methods: We recruited 117 Italian SLE patients. A panel of 34 SNPs in 19 genes involved in immune response, autophagy and inflammation, was selected. SNPs genotyping was performed by allelic discrimination assay by TaqMan assays (Applied Biosystems, Foster City, CA, USA) and ABI PRISM 7000. The main clinical/laboratory features (including injury index and disease activity) were collected on an electronic platform. Remission was defined according to Zen et al. 1 and evaluated over 5 years. A genotype/phenotype correlation analysis was performed. Results: The variant alleles of rs7574965 (STAT4) (p<0.001) and rs2910164 (MIR146a) (p=0.031) were significantly associated with lack of achievement of 5 years remission in SLE. Specifically, patients carrying the C allele of MIR146a were less likely to achieve 5 years remission (p=0.01, OR 0.235, 95% CI 0.074–0.752) as well as to achieve remission after 1, 2 and 3 years of evaluation (p=0.002, p=0.001, p=0.002, respectively). Among the clinical and laboratory features, 5 years remission was less likely to be achieved by patients who had arthritis in their clinical history (p=0.007), and who tested positive for anti-dsDNA (p=0.005). In a multinomial logistic regression analysis, arthritis (p=0.022, Exp(B)=0.255, 95% CI 0.079–0.820), anti-dsDNA (p=0.003, Exp(B)=0.166, 95% CI 0.051–0.537) and MIR146a rs2910164 gene variant (p=0.046, Exp(B)=0.250, 95% CI 0.064–0.974) were confirmed to be independent risk factors for unreached 5 years remission (table 1). Conclusions: We describe for the first time the contribution of STAT4 and MIR146a SNPs as predicting factors for the achievement of 5 years remission in SLE. No genetic study has been performed so far in SLE, while a genetic profile of patients may be useful to predict the disease outcome. Reference: [1] Zen, et al. Ann Rheum Dis. 2017Mar;76(3):562–565. Disclosure of Interest: None declared